PENERAPAN MODEL PEMBELAJARAN ROPES (REVIEW, OVERVIEW, PRESENTATION, EXERCISE, SUMMARY) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF KELAS XI SMA PADA MATERI GELOMBANG BUNYI - Adinda Nurul Aini; Muhammad Nor; Dedi Irawan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The ROPES learning model is a learning model with a complete and interrelated series of activities that can improve students' abilities and active roles in learning. The purpose of this study was to determine the cognitive learning outcomes of class XI high school students by applying the ROPES learning model to sound wave material. The type of research used is experimental research with the